Suicide and the appeals of the soul: reflections on suicide in the Jungian clinic with adolescent patients - Santina Rodrigues de Oliveira (O Mundo da Saúde)
The present paper discusses the autonomy of subjects regarding decisions about life and death, debating the difficulties found by psychotherapists when dealing with this subject, which creates resistances and controversies in contemporary society. The author talks about dealing with suicide according to concepts of analytical psychology, especially C. G. Jung and some post-Jungian authors, which analyzes death as archetypal experience linked to initiatic necessities of transformation of crystallized aspects of personality, and that show up through symptoms connected with the suicidal conception and with self-destructive behaviors. It discusses also the ambiguity of social standards that conveys adolescents and young people both the message of their being autonomous to decide on certain necessities and hindrances to their freedom as regards other subjects, as happens with the sense of life and death. The paper questions the paradigm that guides the practice of health professionals when they identify with the ideals of the classic medical practice, which attributes to itself the responsibility to decide in the patients’ behalf what they must do with their drives, preventing them from being listened as the subjects of their own experience. Lastly, it proposes an approach of suicide allowing patients to establish a metaphorical rapport with death on the basis of symbols observed in unconscious attitudes and fantasies, in order to reach other senses censured both in patients’ discourse and that of their relatives, due to their being dominated by the fear and/ or release concrete death allows them to feel.